2015
DOI: 10.1039/c4cc06126h
|View full text |Cite
|
Sign up to set email alerts
|

Stable dispersions of azide functionalized ferromagnetic metal nanoparticles

Abstract: Ferromagnetic nanoparticles are covalently modified in order to enhance the dispersion stability as well as the antifouling properties. Insertion of an azide moiety allows "click"-reaction of a relevant tag molecule. This and the high saturation magnetization of the presented nanocomposite offer a promising platform for magnetic biosensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Following our observations on the limited growth of PMETAC chains on wood, we believe that electrostatic interactions also hinder the addition of new OFPMA monomers to extend the PMETAC block. This problem has been reported in literature, and it has been shown that in order to build amphiphilic block copolymers comprising a charged block, a salt can be used to screen the charges of the first block during the polymerization of the second block . In our case, with the increase of the ionic strength of the reaction medium, the charges of the PMETAC should have a reduced adverse effect on the polymerization of OFPMA monomers.…”
Section: Resultsmentioning
confidence: 99%
“…Following our observations on the limited growth of PMETAC chains on wood, we believe that electrostatic interactions also hinder the addition of new OFPMA monomers to extend the PMETAC block. This problem has been reported in literature, and it has been shown that in order to build amphiphilic block copolymers comprising a charged block, a salt can be used to screen the charges of the first block during the polymerization of the second block . In our case, with the increase of the ionic strength of the reaction medium, the charges of the PMETAC should have a reduced adverse effect on the polymerization of OFPMA monomers.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to other carbon capsules the hollow carbon nanobubbles presented here consist of aclosed shell of three to four layers of sp 2 -hybridized carbon and thus are highly graphitic. [27] Them etal core enables the selective surface functionalization of the outer capsule wall and furthermore simplifies both surface functionalization and sample purification since it is magnetic. An egatively charged polymer was grown directly from the particles by surface-initiated atom transfer radical polymerization (SI-ATRP) to introduce steric and electrostatic repulsion (Scheme 1and the Supporting Information).…”
mentioning
confidence: 99%
“…Thei nterior of bigger,f ullerene-like graphitic capsules (3-10 nm), consisting of few onion-like oriented graphene layers,i si naccessible for organic molecule cargos (Table S1, entries [23][24][25]. [2c, 23] They often have alow degree of graphitization and consist mainly of amorphous carbon (Table S1, entries [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. [2c, 23] They often have alow degree of graphitization and consist mainly of amorphous carbon (Table S1, entries [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
mentioning
confidence: 99%
See 2 more Smart Citations